2018
DOI: 10.1007/s00261-018-1504-5
|View full text |Cite
|
Sign up to set email alerts
|

Abbreviated mpMRI protocol for diffuse liver disease: a practical approach for evaluation and follow-up of NAFLD

Abstract: An abbreviated mpMRI protocol consisting of liver fat and iron quantification, MR elastography, and VAT measurements is a feasible, less-costly, and accessible option for screening and monitoring of patients with obesity, NAFLD, and metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…Anthropometric measurements were recorded at baseline and follow-up. Abdominal MRI was performed at baseline and at 2 months' follow-up treatment using an abbreviated protocol (25) for the specific purpose of this study. Patients were imaged in a 1.5-T MR scanner (GE 450 W; GE Medical Systems, Milwaukee, WI, USA) in the supine position without the use of intravenous contrast administration.…”
Section: Outcome Measurementsmentioning
confidence: 99%
“…Anthropometric measurements were recorded at baseline and follow-up. Abdominal MRI was performed at baseline and at 2 months' follow-up treatment using an abbreviated protocol (25) for the specific purpose of this study. Patients were imaged in a 1.5-T MR scanner (GE 450 W; GE Medical Systems, Milwaukee, WI, USA) in the supine position without the use of intravenous contrast administration.…”
Section: Outcome Measurementsmentioning
confidence: 99%
“…In a prospective study with 25 patients, Cunha et al (45) used an abbreviated MRI protocol to analyze quantitative imaging features and assessed its use during treatment of patients with obesity and nonalcoholic fatty liver disease. All patients were referred for MRI evaluation during the course of a physical activity program for overweight and obesity treatment and underwent quantitative analysis of liver fat and iron content, liver stiffness, and visceral adipose tissue.…”
Section: Assessment Of Liver Fat and Fibrosis-non-mentioning
confidence: 99%
“…The abbreviated MRI protocol took less than 10 minutes to complete. Cunha et al (45) concluded that it represents a feasible, less costly, and accessible option for screening and monitoring patients with obesity, nonalcoholic fatty liver disease, and metabolic syndrome. Although no data exist with regard to use of abbreviated MRI protocols for iron overload, a reasonable protocol would focus on only the assessment of iron overload, without use of all of the other conventional sequences within a full contrast-enhanced MRI protocol.…”
Section: Assessment Of Liver Fat and Fibrosis-non-mentioning
confidence: 99%
“…The abbreviated MRI exam has been embraced in the radiology community as an important and valuable initiative. Current studies focusing on the role of MRI in screening and surveillance have developed specialized protocols that are often abbreviated with applications in the prostate and liver . Variable imaging protocols have been used and in general show a similar diagnostic performance compared with the full protocol for the detection of occult malignancies.…”
Section: Abbreviated Mri As a Valuable Initiativementioning
confidence: 99%
“…Current studies focusing on the role of MRI in screening and surveillance have developed specialized protocols that are often abbreviated with applications in the prostate and liver. [85][86][87][88][89][90][91][92] Variable imaging protocols have been used and in general show a similar diagnostic performance compared with the full protocol for the detection of occult malignancies. Other novel applications include using abbreviated MRI in the pediatric population to decrease the duration of necessary sedation, and as a rapid and accurate imaging tool in the musculoskeletal setting to detect fractures and increase patient throughput in an emergency setting.…”
Section: Abbreviated Mri As a Valuable Initiativementioning
confidence: 99%